Changing attitudes: The impact of Expert by Experience involvement in Mental Health Nursing Education: An international survey study. (3rd November 2018) - Happell, Brenda; Platania‐Phung, Chris; Scholz, Brett; Bocking, Julia; Horgan, Aine; Manning, Fionnuala; Doody, Rory; Hals, Elisabeth; Granerud, Arild; Lahti, Mari; Pullo, Jarmo; Vatula, Annaliina; et al.
Abstract: Reform to nursing education is essential to ensure future generations of nurses are strongly positioned to value, know, and deliver strength‐based, recovery‐oriented mental health practice. A promising pathway to effectively drive reform is the coproduction of curricula by nursing academics and people with lived experience of recovery from mental distress referred to as Experts by Experience. The Co‐production in Mental Health Nursing Education (COMMUNE) project is an international collaboration for development and implementation of consumer coproduced curricula. This study evaluated the inclusion of Expert by Experience‐led mental health nursing education on nursing students' attitudes to people labelled with mental illness, mental health nursing, and consumer participation. A repeated self‐report measures design was implemented in Australia, Ireland, and Finland to ascertain level of generalizability of consumer involvement within undergraduate nursing programmes. Data were collected from nursing students ( n  = 194) immediately before and after the education module, using three self‐report instruments on attitudes (Mental Health Nurse Education Survey, Consumer Participation Questionnaire, and Opening Minds Scale). Data were analysed using descriptive and inferential statistics. Eighty‐nine per cent of the 27 points of change reflected more favourable and accepting attitudinal change. Of these, 41% were significant at Bonferroni adjusted alpha of 0.0025. There was a statistically significant increase in preparedness for practice in the mental health field in each of the three countries. The most pronounced change is related to the social and systemic inclusion of people with a diagnostic label and recovery‐oriented care more broadly.